A rational design strategy for red thermally activated delay fluorescence emitter employing 2, 1, 3-benzothiadiazole skeleton with asymmetric structure. (December 2021) - Huo, Jinnan; Zheng, Yanan; Zhang, Di; Xu, Huixia; Li, Yanbo; Miao, Yanqin; Shi, Heping; Tang, Ben Zhong
Abstract: Organic light-emitting diodes (OLEDs) employing thermally activated delayed fluorescence (TADF) can effectively utilize triplet excitons without the noble-metal doping. However, there are challenges in the design of adjusting the competition between the narrow band gap and the non-radiative transition of red TADF emitters. Herein, a red emitter named as 4-(3, 5-di(9 H -carbazol-9-yl)phenyl)-7-(9, 9-dimethylacridin-10(9 H )-yl)benzo[ c ] [1, 2, 5]thiadiazole (BCZ-BTD-AD) with an asymmetric structure containing 2, 1, 3-benzothiadiazole (BTD) as the electron-acceptor, 9, 10-dihydro-9, 9-dimethylacridin and 1, 3-di(9 H -carbazol-9-yl)benzene as the electron-donors was designed and synthesized. The twisted conformation and large rigid plane endow the compound TADF and aggregation-induced emission (AIE) characteristics, as well as a high thermal decomposition temperature ( T d ) of 419 °C. Pure red non-doped OLED (device A) shows the maximum emission peak at 652 nm with the commission internationale de l'eclairage (CIE) coordinates of (0.63, 0.32), the turn-on voltage ( V on ) of 3.6 V, the maximum brightness ( L max ) of 1728.9 cd m −2, the maximum current efficiency ( η C ) of 1.6 cd A −1, the maximum power efficiency ( η P ) of 1.2 lm W −1 and the maximum external quantum efficiency ( η ext ) of 2.3%. Doped OLED (device B) constructed based on BCZ-BTD-AD doped 20% in CBP shows performance with the maximum emission peak of 628 nm, the CIE coordinates of (0.53, 0.37), the turn-on voltage of 3.2 V, the maximum brightness of 1883.9 cd m −2, the maximum current efficiency of 6.8 cd A −1, the maximum power efficiency of 5.0 lm W −1 and the maximum external quantum efficiency of 5.6%. Graphical abstract: Image 1 Highlights: A red emitter (BCZ-BTD-AD) with an asymmetric structure containing 2, 1, 3-benzothiadiazole was designed and synthesized. BCZ-BTD-AD shows both thermally activated delayed fluorescence (TADF) and aggregation-induced emission (AIE) properties. The non-doped OLED based on BCZ-BTD-AD exhibits pure red emission of 652 nm with CIE coordinates of (0.63, 0.32).